The war on drugs and the global colour line - Koram, Kojo (Pluto Press, 2019)
"Fifty years of the War on Drugs has led to millions of deaths, displacements, and incarcerations. Disproportionately enacted on oppressed races, international drug prohibition has reinforced the color line across the globe. This collection reveals the racist impact of the war on drugs across multiple continents and in numerous situations, from racialized drug policing at festivals in the United Kingdom to the necropolitical wars in Juarez, Mexico, and from the exchange of drug policing programs between the United States and Israel to the management of black bodies in Brazil. Pushing forward the debate and activism led by groups such as Black Lives Matter and calling for radical changes in drug policy legislation and prison reform, this collection proves that the problem of drugs and race is an international, and intentional, disaster"--